EIF2AK4 mutations cause pulmonary veno-occlusive disease, a recessive form of pulmonary hypertension - Eyries, Mélanie; Montani, David; Girerd, Barbara; Perret, Claire; Leroy, Anne; Lonjou, Christine; Chelghoum, Nadjim; Coulet, Florence; Bonnet, Damien; Dorfmüller, Peter; Fadel, Elie; Sitbon, Olivier; et al. (Nature genetics, 2014)
Florent Soubrier and colleagues identify biallelic mutations in EIF2AK4 as a major cause of pulmonary veno-occlusive disease, a rare form of pulmonary hypertension. EIF2AK4 encodes a serine-threonine kinase, and the disease-causing mutations are predicted to result in loss of protein function. Pulmonary veno-occlusive disease (PVOD) is a rare and devastating cause of pulmonary hypertension that is characterized histologically by widespread fibrous intimal proliferation of septal veins and preseptal venules and is frequently associated with pulmonary capillary dilatation and proliferation 1 , 2 . PVOD is categorized into a separate pulmonary arterial hypertension–related group in the current classification of pulmonary hypertension 3 . PVOD presents either sporadically or as familial cases with a seemingly recessive mode of transmission 4 . Using whole-exome sequencing, we detected recessive mutations in EIF2AK4 (also called GCN2 ) that cosegregated with PVOD in all 13 families studied. We also found biallelic EIF2AK4 mutations in 5 of 20 histologically confirmed sporadic cases of PVOD. All mutations, either in a homozygous or compound-heterozygous state, disrupted the function of the gene. These findings point to EIF2AK4 as the major gene that is linked to PVOD development and contribute toward an understanding of the complex genetic architecture of pulmonary hypertension.